Development of cancer immunotherapy based on PD-1/PD-L1 pathway blockade. Issue 58 (22nd October 2019) - Zhang, Min; Liu, Kehai; Wang, Mingfu
Abstract : The possible reasons that caused low response rate and severe side effects of programmed death receptor 1 (PD-1)/programmed death ligand 1 (PD-L1) blockade therapy and corresponding strategies. Abstract : Programmed death receptor 1 (PD-1)/programmed death ligand 1 (PD-L1) blockade therapy has achieved considerable success in various tumours. However, only a fraction of patients benefit from its clinical application, and some patients might be suffer from tumour resistance against PD-1/PD-L1 blockade therapy after the original response. In this review, we summarized the main reasons that caused the low response rate of PD-/PD-L1 blockade therapy: firstly, the off-target of PD-1/PD-L1 blocking agents, which is also the main factor of the side effect of autoimmune disorders; secondly, the insufficient infiltration of T cells in a tumour microenvironment; thirdly, the low immunogenicity of tumor cells; fourth, other immunosuppressive components impairing the therapeutic efficacy of the immunotherapy based on the PD-/PD-L1 blockade, and introducing some updated the delivery system of PD-1/PD-L1 blocking agents and the combination therapy based on PD-1/PD-L1 inhibitors and other therapeutics that can complement and promote each other to achieve improved immune response.